Effect of mycorrhizae application on the growth performance of paddy (Oryza sativa) / Aicah Patuhai - Patuhai, Aicah (Faculty of Plantation and Agrotechnology, 2015)
A greenhouse trial was carried out to find out the effect of paddy (Oryza sativa) growth performance with different rate of mycorrhiza treated. Paddy were cultivated with application of four levels of mycorrhiza (mycogold®) Treatment 1 is control treatment, Treatment 2 is 20 g per pot, Treatment 3 is 40 g per pot and Treatment 4 is 60 g per pot with five replication using a Complete Randomize Design (CRD). The growth performance data which are the number of leaves and number of tillers were collected once a week until harvesting time at week 13. Other data such root weight, number of panicles, 100 grain weight and total grain weight was recorded on the last week of experiment. Meanwhil e, the soil sample was analyzed every two week until harvesting time. The results showed Treatment 4 is 60 g of mycorrhiza per pot gave the best performance . Therefore the amount of mycorrhiza suggested was Treatment 4 with 60 g of mycorrhiza per pot in order to get the best performance and yield of paddy.